A tale of two genera: exotic Eucalyptus and Acacia species in China. 1. Domestication and research. (1st March 2020) - Arnold, R.J.; Xie, Y.J.; Luo, J.Z.; Wang, H.R.; Midgley, S.J.
In China a substantial plantation industry, including 5.4 M ha of eucalypts and up to 50, 000 ha of acacias, has been built on a foundation of R&D and germplasm acquisition for exotic eucalypt and acacia species over the past 40 years. From the 1980s through to the early 2000s a suite of Chinese-Australian collaborative R&D projects made major contributions to domestication, genetic improvement, silviculture and other aspects of plantation eucalypts and acacias in southern China. Even today, germplasm derived from earlier projects still provides the majority of planting stock deployed in China's current eucalypt plantations. For eucalypts, improvements in plantation productivities have been achieved through solid, well managed R&D programs. For acacias, despite work done in past decades to develop breeding populations and production capacities for improved seeds, genetic resources of acacias in China have deteriorated greatly in recent years. Factors affecting domestication and genetic improvement of both genera in China are reviewed in this report along with the research undertaken for both genera over the past 40 years.